Ammonia volatilization from coated urea in irrigated brachiaria crop - Cascaldi, Alexia Morello da Silva [UNESP]; de Faria, Rogério Teixeira [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Dos Santos, Miquéias Gomes [UNESP]; Filho, João Alberto Fischer; Cazetta, Jairo Osvaldo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2020)
Nitrogen is an essential nutrient for crops, however its use is subject to many losses in the soil-plant-atmosphere system. Thus, some compounds have been used for the purpose of reducing these losses, increasing the efficiency of nitrogen fertilizers. The objective of this work was to verify the effect of NZone Max® nitrogen stabilizer on N losses through ammonia volatilization and nitrate leaching, in an Urochloa brizantha cv. Marandu crop. A field experiment was carried out in Jaboticabal – SP, and treatments consisted of 4 irrigation depths (0.20, 0.40, 0.60 and 0.80 of the reference evapotranspiration), with and without nitrogen stabilizer added to applied urea. The treatments were arranged in a split-plot strip design, with irrigation depths in the plot and stabilizer in the subplot, with 4 replications. The following variables were measured: ammonia volatilization rate, nitrate, ammonium, N-total, pH and electrical conductivity of the soil solution. The volatilization rate of ammonia reached the highest values on the third day after fertilization. At that moment, the lower irrigation depth presented a higher rate of volatilized ammonia, while the higher depth presented the lowest volatilization. There was no significant effect of NZone Max® for the analyzed variables.
Volatilização de amônia proveniente de ureia protegida em braquiária irrigada
Keywords: Irrigation; Nitrogen; Pasture; Urochloa brizantha